2015
DOI: 10.1182/blood.v126.23.4660.4660
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Carica Papaya leaf Extract on Platelet Count in Chronic Immune Thrombocytopenic Purpura: A Case Series

Abstract: Background: The leaves of Carica papaya have been used to treat thrombocytopenia in the critical phase of Dengue fever in areas where the virus is endemic. This case series describes the use of C. papaya leaf liquid extract (CPLE) as an adjunctive therapy for four patients receiving standard-of-care treatment for chronic immune thrombocytopenic purpura (ITP). Case 1: A 67 yo M diagnosed with ITP in 1999 presented on 8/17/2013 with bruising and a platelet count of 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Oral consumption of C. papaya leaf is generally well tolerated across a variety of formulations (mostly as juice and aqueous extract) in adults though high-quality and comprehensive safety data has not been well documented. C. papaya leaves were mostly administered for a short duration of up to five days [ 6 , 32 – 34 , 36 , 37 , 39 – 44 , 48 , 49 ], though longer durations of administration have been reported to be tolerable [ 46 ]. Based on the published literature, mild gastrointestinal disturbances were most commonly reported [ 5 , 6 , 32 – 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Oral consumption of C. papaya leaf is generally well tolerated across a variety of formulations (mostly as juice and aqueous extract) in adults though high-quality and comprehensive safety data has not been well documented. C. papaya leaves were mostly administered for a short duration of up to five days [ 6 , 32 – 34 , 36 , 37 , 39 – 44 , 48 , 49 ], though longer durations of administration have been reported to be tolerable [ 46 ]. Based on the published literature, mild gastrointestinal disturbances were most commonly reported [ 5 , 6 , 32 – 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…CPLE was found to increase the platelet count in both adult and pediatric dengue patients. 144 Clinical studies have revealed that CPLE administration three times a day increased the rate of platelet recovery, along with a statistically significant rise in platelet counts in the CPLE-receiving group from day 3. The exact mechanism of CPLE is yet to be uncovered; however, it has been observed that CPLE can elevate the expression of CD110 (known as the thrombopoietin receptor) on megakaryocytes and platelets, which is essential for platelet formation and megakaryocyte proliferation.…”
Section: Therapeutics For Denguementioning
confidence: 99%
“…For five days in a succession, a patient with dengue infection got 25 mL of aqueous CPLE twice a day [47]. As a result, the platelet count rose from 55 to 168 x 10 3 /ml [92].…”
Section: Benefits Drawbacks and Limitationsmentioning
confidence: 99%